Two newly-emerging substituted phenethylamines MAL and BOD induce differential psychopharmacological effects in rodents. (September 2020) - Custodio, Raly James Perez; Sayson, Leandro Val; Botanas, Chrislean Jun; Abiero, Arvie; Kim, Mikyung; Lee, Hyun Jun; Ryu, Hye Won; Lee, Yong Sup; Kim, Hee Jin; Cheong, Jae Hoon
Background: Recently, the recreational use of substituted phenethylamines has grown rapidly. Among these are 2-(3, 5-dimethoxy-4-((2-methylallyl)oxy)phenyl)ethanamine (MAL) and 2-(2, 5-dimethoxy-4-methylphenyl)-2-methoxyethan-1-amine (BOD). However, studies characterizing their abuse potential are still lacking. Aim: The purpose of this study was to investigate the abuse potential of MAL and BOD. Methods: The psychostimulant, reinforcing, and rewarding properties of MAL and BOD were analyzed using locomotor sensitization, self-administration, and conditioned place preference tests. Dopamine antagonists (i.e. SCH23390, haloperidol) were administered during conditioned place preference to evaluate the involvement of the mesolimbic dopamine system. Furthermore, dopamine-related protein expression in the nucleus accumbens and the ventral tegmental area was measured along with dopamine concentrations in the nucleus accumbens. Electroencephalography was conducted to determine effects of MAL and BOD on brain wave activity. Results: MAL induced psychostimulant effects and sensitization, while BOD induced locomotor depression in mice. Only MAL was self-administered by rats. Both drugs induced conditioned place preference in mice at different doses; dopamine receptor antagonists blocked MAL- and BOD-induced conditioned place preference. Both the compounds altered the expression of dopamine receptor D1 and D2 proteins in the nucleus accumbens and tyrosine hydroxylase (TH) and dopamine transporter in the ventral tegmental area, enhanced dopamine levels in the nucleus accumbens, and increased delta and gamma wave activities in the brain. Conclusions: MAL may induce abuse potential via the mesolimbic dopaminergic system and possibly accompanied by alterations in brain wave activity. Moreover, the lack of rewarding and reinforcing effects in BOD suggest that this drug may have little to no capability to engender compulsive behavior, though having found to induce alterations in dopaminergic system and brain wave activities.